A mental disorder of a kind or degree warranting confinement: examining justifications for psychiatric detention - Bartlett, Peter (Taylor Francis, 2012)
It has long been the case in jurisprudence under the European Convention on Human Rights that mental disorder must be of a certain severity in order to justify detention, but there has been little meaningful debate as to what that means. The question is relevant not merely to the European Court of Human Rights, but also to the Committee for the Prevention of Torture, as the potential of inhuman or degrading treatment that arises from the coercive elements in institutions is particularly clear if persons are wrongfully detained in an institution and ought in fact to be somewhere else. Considerable improvement in the substantive clarity of domestic law is therefore required. The specifics of the domestic standards are a matter for individual governments but, within the Council of Europe, they will need to meet the requirements of both the European Convention on Human Rights and the United Nations Convention on the Rights of Persons with Disabilities. The article considers the traditional justifications for civil detention in psychiatry – dangerousness, need for treatment and capacity – in the light of these two conventions.